Jesus : uncovering the life, teachings, and relevance of a religious revolutionary - Borg, Marcus J. ([San Francisco] : HarperSanFrancisco, 2006)
Almost two thousand years after his death, Jesus continues to be front-page news in the United States. Yet American Christians are deeply divided about what it means to follow him. Bible scholar Borg takes us on a journey to discover who Jesus was, what he taught, and why he still matters today. Borg argues that how we see Jesus affects how we see Christianity and reveals a new way of seeing--a new perspective that can overcome the differences between the literalists and progressives, a path that emphasizes following "the way" of Jesus, the original name of the Jesus movement. Jesus remains the decisive revelation of God, but we now encounter him as both a reality and a role model centered in God, focused on both personal and political transformation, emphasizing practices rather than beliefs, and exemplifying a faith characterized by deep commitment and gentle certitude.--From publisher description.
Jesus today : telling his story -- The Gospels : memory and testimony -- The Gospels : memory, metaphor, and method -- The shaping of Jesus : Jewish tradition in an imperial world -- The shaping of Jesus : his experience of God -- The big picture : the synoptic profile of Jesus -- God : God's character and passion -- Wisdom : the broad way and the narrow way -- Resistance : the Kingdom and the domination system -- Executed by Rome, vindicated by God -- Jesus and American Christianity today.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- Historicity; Jesus Christ -- Teachings; Jesus Christ -- Significance